Identification of Active Compounds on Muntingia calabura L.Leaves using Different Polarity Solvents - Sri Adelila Sari; Mellya Ernita; M Nasir Mara; Muhammad Rudi AR (Universitas Negeri Medan, 2020)
Plant of Muntingia calabura L are often known as kersen, seri or cherry. Leaves of Muntingia calabura L. contains many benefits but its properties are still little known to the public. It contains secondary metabolites which have many uses. This study was aimed to determine the content of secondary metabolites in this leaf. Leaves extracts were obtained by maceration extraction for 3 times 24 hours using polar, semi-polar and non-polar solvents to determine the solubility of secondary metabolite compounds in each solvent. The solvents used were ethanol, ethyl acetate and n-hexane. The leaveswere dissolved a lot in polar solvents, marked by the formation of a dark green color in ethanol-series extracts, the color fades more in semi-polar and non-polar solvents. The three leaves extracts were tested for secondary metabolite contents by phytochemical screening tests. Phytochemical screening was an initial selection stage to detect classes of chemical compounds contained in plant. Phytochemical screening were included alkaloid, terpenoid, steroid, tannin, flavonoidand saponin tests. Based on the results of phytochemical screening tests, the leaf was contained several secondary metabolite compounds, namely flavonoids, saponins, steroids, terpenoids, alkaloids, phenols and tannins.